Pengaruh Partisipasi, Transparansi dan Akuntabilitas pada Pengelolaan Keuangan Dana Desa ( Studi Kasus pada Desa di Kecamatan Banyuates Kabupaten Sampang) - Nur Halisa; Nur Diana; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the Effect of Participation, Transparency and accountability on Village Fund Management in Banyuates District, Sampang Regency. The method of distribution of questionnaires is the type of research that is used. The SPSS software was used to process the data in this study, which included 100 village and community officials as the sample. Validity and reliability requirements have been met by this study. Examination of the information utilized in this review is elucidating factual investigation, old style presumption test, different linier relapse, speculation testing and investigation of the coefficient of assurance. The variable utilized in this study are town store the executives variable (subordinate variable), while the free factors are Support, Straightforwardness and responsibility.            The results of this study conclude that the participation variable has a partial effect on the management of village funds, transparency variable has a partial effect on the management of village funds and accountability variable has a partial effect on the management of village funds. Keyword; Village fund management, participation, transparency and accountability